On - Farm Evaluation of Natural Toxicants from Tephrosia Vogelii and Petiveria Alliacea on Megalurothrips Sjostedti and Apion Varium of Cowpea (Vigna Unguiculata (L) Walp) (Bangladesh Journal of Agricultural Research, 2012)
The field study was conducted during the planting season of cowpea to evaluate the natural toxicant from Tephrosia vogelii and Petiveria alliacea and their mixture against Megalurothrips sjostedti and Apion varium at three different   concentrations (5, 10, and 20% v/v). The experiment was set up in randomized complete block design. The field observations showed that the two insect pests were effectively controlled by the botanical insecticides compared with untreated plants. Also, the plant extracts at 20% and 10% v/v significantly protected cowpea pods and grains from the damage. However, higher grain yield was obtained from the plant treated with 20% v/v compared to those treated with 10%, 5% v/v and untreated plants. Combination of the two plant extracts at 20%   v/v had the same efficacy with synthetic insecticide (Decis). Thus, these plant   extracts can be used in organic farming.   DOI: http://dx.doi.org/10.3329/bjar.v36i4.11745   Bangladesh J. Agril. Res. 36(4): 575-582, December 2011